2021
DOI: 10.1002/jmv.27059
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of IgG antibodies kinetics after severe and critical COVID‐19

Abstract: The kinetics of IgG antibodies after coronavirus disease 2019 (COVID‐19) remain poorly understood. We investigated factors influencing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) IgG antibody levels and time to seronegativation during the follow‐up of severe and critically ill patients. We retrospectively reviewed serological evaluations drawn during the follow‐up of severe or critical laboratory‐proven COVID‐19 patients hospitalized at a large academic hospital. Specific IgG titers were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Varona et al, found that seropositive healthcare workers of the Spanish Hospitals Group remained seropositive after 9 months but with a significant decline in antibody titers and two distinct antibody dynamic profiles were identified (declining vs. stable). Independent factors associated with longer persistence of antibodies were symptomatic infection and higher exposure to COVID-19 patients [ 24 , 28 , 29 ], age, BMI, and immunosuppression [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varona et al, found that seropositive healthcare workers of the Spanish Hospitals Group remained seropositive after 9 months but with a significant decline in antibody titers and two distinct antibody dynamic profiles were identified (declining vs. stable). Independent factors associated with longer persistence of antibodies were symptomatic infection and higher exposure to COVID-19 patients [ 24 , 28 , 29 ], age, BMI, and immunosuppression [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of specific antibodies in patients with a history of COVID-19 linked the immune response to various factors, including disease stage and severity, age, and comorbidities. While IgG antibodies can be detected in a vast majority of COVID-19 patients 10 days after the infection, their levels generally decrease over time [4][5][6][7]. Similar patterns in antibody dynamics could be predicted after vaccination [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 94%
“…Following SARS-CoV-2 infection, immunocompetent patients rapidly develop specific antibodies, whose levels generally show a positive correlation with disease severity [3][4][5][6][7]. Relatively high antibody levels in severe COVID-19 raise the question of their efficiency in immune defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early investigations of infection-induced responses for diagnostic purposes included evaluation of IgA, IgM and IgG humoral immunity ( Ma et al, 2020 ; Bichara et al, 2021 ; Maeda et al, 2021 ) and many commercial kits have been developed for these endpoints. SARS-CoV-2 specific IgA seems to be a high performing early diagnostic endpoint ( Ma et al, 2020 ; Sterlin et al, 2021 ), while the kinetics of post-infection IgM and IgG better reflect peak and waning immunity in convalescent cohorts ( Bichara et al, 2021 ; Duysburgh et al, 2021 ; De Greef et al, 2021 ). Interestingly, some studies have observed pro-inflammatory IgG subsets (IgG1 and IgG3) trend higher with severity of clinical COVID-19 disease while others (IgG2 and IgG4) are rarely detected ( Yates et al, 2021 ; Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%